Missed Opportunities for Prevention of Mother-to-Child Transmission of Human Immunodeficiency Virus. Issue 4 (April 2017) - Scott, Gwendolyn B.; Brogly, Susan B.; Muenz, Daniel; Stek, Alice M.; Read, Jennifer S.
Abstract : OBJECTIVE: To identify missed opportunities for prevention of mother-to-child transmission of human immunodeficiency virus (HIV). METHODS: Data regarding HIV-infected children born between 2002 and 2009 to HIV-infected women enrolled in the U.S. International Maternal Pediatric Adolescent AIDS Clinical Trials prospective cohort study (protocol P1025) were reviewed. The characteristics of the HIV-infected infants and their mothers and the mothers' clinical management are described. RESULTS: Twelve cases of mother-to-child transmission of HIV occurred among 1, 857 liveborn neonates, for a prevalence of 0.65 per 100 live births to HIV-infected women (95% confidence interval 0.33–1.13). Four transmissions occurred in utero, three were peripartum transmissions, and the timing of transmission for five neonates was unable to be determined. None were breastfed. Seven women had plasma viral loads greater than 400 copies/mL near delivery. Six women had less than 11 weeks of antiretroviral therapy during pregnancy; three of these women had premature deliveries. One woman received no antiretroviral therapy during pregnancy because she was diagnosed with HIV postpartum. Six had poor to moderate adherence to antiretroviral therapy. Four of the five mothers with viral loads greater than 1, 000 copies/mL delivered preterm neonates. There were five women who delivered by cesarean; four were nonelective cesarean deliveries and only one was an elective cesarean delivery for HIV prevention. CONCLUSION: Despite access to high-level care and follow-up, a small proportion of HIV-infected women transmitted the virus to their neonates. This case series provides insight into factors contributing to HIV perinatal transmission and can inform the development of new strategies for prevention of mother-to-child transmission of HIV. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00028145. Abstract : Avoidable causes of mother-to-child human immunodeficiency virus transmission include inadequate control of maternal viral load from poor medication adherence, short duration of therapy, and late maternal human immunodeficiency virus diagnosis.Supplemental Digital Content is Available in the Text.